Automatic Liquid Filling in Deep Water Culture Hydroponic System Based on Water Level and TDS Meter Value - Ahmad Faiz Al Hakam; Riky Dwi Puriyanto (Universitas Ahmad Dahlan, 2022)
Currently, the filling of nutrient fluids for hydroponic systems is still carried out manually or conventionally. In this study, an automatic liquid filling system was made in the DWC hydroponic system based on water level and TDS Meter values. The controlling process uses an Arduino Uno microcontroller. The sensor is used to perform readings of nutrient values using a TDS sensor, for the measurement of water level distances using an ultrasonic sensor HC-SR04. The 16x2 LCD is used to display distance values and TDS values. Meanwhile, to drain nutrient fluids using a 12V pump. The results of this study the system as a whole can carry out the process of filling nutrient fluids automatically when the water level distance is >3.5 cm or the TDS value <700 PPM. Meanwhile, if the water level distance is <3.5 cm and the TDS value is >700 PPM, the pump will turn off. The result of this study was that the ultrasonic sensor HC-SR04 got an average error value of 0.12%. TDS sensors get an average error value of 6.02%.